Nigeria's Policy towards South Africa (1960-1979). - Bakare, Kolawole Muheeb (Obafemi Awolowo University, 2014)
Nigeria's policy towards South Africa's obnoxious apartheid system is the focus of this study. Pinpointing and examining some of the factors responsible for the country's stance on apartheid policy, this four chapter study lays emphasis on Nigeria's stand against apartheid.